Physical Education Association - United Kingdom centenary conference abstracts 1999 (1999)
United Kingdom Physical Education Association - centenary conference abstracts (University of Bath, 8-11 April, 1999). Content: - Physical education teachers and their careers - Kathleen M. Armour - Beyond romantic views of the self: Critical autobiography as a challenge to teacher development - Andrew C. Sparkes - New agendas for the new millennium? - Dawn Penney - Opportunities for learning experienced by a group of PGCE students in their school based work. - Peter Breckon - Physical activity promotion in schools: Physical education.Teachers views. - Lorraine Cale - Teaching cricket under sport education: An Australian perspective. - Alex Cameron and Andrew Taggart - Identities and subcultrues in relation to sport: An analysis of teenage girls' magazines. - Claudia Cockburn - The importance of physical education and regualr exercise for young people with insulin dependent diabetes melitus. - Elizabeth Marsden - Sherborne development movement for all children. - Elizabeth Marsden - 'Examining' the changing nature of PE teachers' work. - Gareth Nutt - The 'socio-moral' dimension of physical education: A critical review. - Andrew Theodoulides & Kathleen Armour - Developing an educational rather than a training enterprise: A partnership of meaning and provision. - Mike Waring - Managing a department: The role of continued professional development in the career of a physical education teacher - Andrew Theodoulides.